THD and efficiency study for PV grid-connected - Lafsah, Mat Daud (2012)
Total harmonic distortion (THD) is a measurement of the harmonic distortion and is defined as the ratio of the sum of the powers of all harmonic components to the power of the fundamental frequency. In general, efficiency is a measurable concept, quantitatively determined by the ratio of output to input. The project is all about the experimental study on THD and efficiency for photovoltaic (PV) grid connected. A scale-down less than 1kW system will be developed and established for the study. The impact on THD and efficiency will be assessed to the real network environment by connected three phase motor to Variable Frequency Drives (VFD’s) as the load. The experimental will be done by using Power Quality Analyzer (PQA) software and the comparison between before and after connected PV will be conducted. The results of the THD and efficiency for PV grid connected system will be obtained and analyzed under influence of load conditions.